2022
DOI: 10.3389/fimmu.2022.984984
|View full text |Cite
|
Sign up to set email alerts
|

Global scientific trends on the immunomodulation of mesenchymal stem cells in the 21st century: A bibliometric and visualized analysis

Abstract: BackgroundSince the discovery of the immunomodulatory functions of mesenchymal stem cells (MSCs), their application in immunomodulation has attracted considerable attention, and an increasing number of studies have been conducted worldwide. Our research aimed to investigate the global status and trends in this field.MethodsPublications on the immunomodulatory functions of MSCs from 1 January 2000 to 7 March 2022 were retrieved from the Web of Science Core Collection. The data were studied and indexed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The CiteSpace [ [10] , [11] , [12] ] (version 6.1.R3, developed by Chaomei Chen in Philadelphia, PA, USA) and VOSviewer [ [13] , [14] , [15] ] (version 1.6.18, developed by CWTS Meaningful Metrics in Leiden, Netherlands) software were used for scientometric and bibliometric analysis, respectively. The primary study authors, regions/countries, institutional cooperation, and future research trends were obtained by evaluating the centrality intensity and co-occurrence visualization diagrams.…”
Section: Methodsmentioning
confidence: 99%
“…The CiteSpace [ [10] , [11] , [12] ] (version 6.1.R3, developed by Chaomei Chen in Philadelphia, PA, USA) and VOSviewer [ [13] , [14] , [15] ] (version 1.6.18, developed by CWTS Meaningful Metrics in Leiden, Netherlands) software were used for scientometric and bibliometric analysis, respectively. The primary study authors, regions/countries, institutional cooperation, and future research trends were obtained by evaluating the centrality intensity and co-occurrence visualization diagrams.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, MSCs-therapy spread as an effective tool for a range of autoimmune and immune-mediated inflammatory diseases [ 14 ]. MSCs were found to exhibit a unique immunoregulatory effect on immune cells, i.e., T- and B-lymphocytes, NK-cells, macrophages and dendritic cells [ 15 ]. Since 2000, both experimental and clinical studies have shown the effectiveness of MSC transplantation for graft-versus-host disease (GVHD), systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), and inflammatory bowel disease (IBD) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“… 13 This type of research employs mathematical and statistical tools to explicitly and statistically analyze the scientific movement, including the interrelationships between countries, institutions, authors, journals, and keywords. 14 Additionally, bibliometric analysis has been applied to mesenchymal stem cells on immunomodulatory functions, 15 single-cell sequencing on immune cells. 16 However, a bibliometric analysis of anesthetics drugs’ impact on immune function has not been reported in the literature thus far.…”
Section: Introductionmentioning
confidence: 99%